Development of a real time system for monitoring of swimming performance - Le Sage, Tanya; Bindel, Axel; Conway, Paul; Justham, Laura; Slawson, Sian; West, Andrew (Procedia engineering, 2010)
This research was conducted to allow real-time transmission, processing and presentation of data to swimming coaches and subsequently their swimmers in a training environment. This was done using an integrated system which comprised of a wireless sensor node, vision components and both force and pressure measurement technologies. Filtering approaches and signal processing algorithms were used to allow real-time data analysis on the node. Immediate feedback to the coach and sports scientist on poolside allows for a swimmer to be given quantifiable coaching tips and enables them to adjust their performance based on the results obtained. The system has reduced the time for processing acquired data and has delivered novel monitoring devices suitable for the harshness of the pool environment.